ANALISIS TINGKAT BEBAN KERJA MENTAL DENGAN METODE NASA-TLX INDEX DAN BEBAN KERJA FISIK BERDASARKAN KEBUTUHAN KALORI PADA PEKERJA BAGIAN PRODUKSI PT.NATRACO SPICES INDONESIA, PADANG, SUMATERA BARAT - , Anggia Paramitha, Antonius Kurniawan , Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Workload according to Meshkati in Astianto and Suprihhadi (2014) can be defined as a difference between the capacity or ability of workers and the demands of the work that must be faced. Given that human work is mental and physical, each has a different level of loading. A loading level that is too high allows excessive energy use and overstress occurs, whereas a loading intensity that is too low allows boredom or under stress. This study aims to measure the level of physical and mental workload at PT. Natraco Spices Indonesia helps HRD make decisions regarding the division of labor and rotation of workers so that it can help companies increase productivity while improving work patterns. The research population this time was all production floor workers at PT. Natraco Spices Indonesia, totaling 73 people. Primary data was obtained by distributing questionnaires and field observations for approximately 1 month and interviewing several workers and the HRD responsible at the location. The results showed that: (1) The level of physical workload of workers on the production floor was at medium level and above it is become a concern to make rotating workers or adding tools to assist the production process, (2) The level of mental workload on production floor workers at PT. Natraco Spices Indonesia was at medium level and above, this is very worrying because if it is not addressed further it can disrupt productivity so that it disrupts the entire production process. Keywords: mental workload, physical workload, NASA-TLX, level of caloric needs